Struktur Produksi Bunyi Bahasa Anak Usia 2 Tahun (Studi Kasus Ilyas) - Rudi Karma; Samsuddin, Samsuddin; Sulpina, Sulpina (GERAM: Gerakan Aktif Menulis, 2023)
The production structure of sound in language by 2-year-old children is an interesting issue in the realm of language research. It lies in the imperfect yet meaningful language production of children. In their language production, some sound omissions and changes occur. This research aims to describe the structure of sound production in 2-year-old children. It is a field research conducted using a qualitative descriptive method. The research findings indicate that the structure of sound production involves sound omissions and changes. Sound omissions occur in consonant sounds such as [r], [m], [n], [ŋ], [t], [k], and [l]. Sound changes occur in sounds such as [t→c], [s→c], [au→o], and [ai→e]. These omissions and changes consistently occur